Threat of Dengue Outbreak in Nepal in Context of COVID-19 Pandemic - Koirala, Pallavi; Tamrakar, Dipesh (Journal of Lumbini Medical College, 2020)
The world has been chained with Corona Virus Disease (COVID-19) pandemic today. It has affected more than 200 countries in just about a few months since December 2019. The virus has engulfed the world at a momentum never seen before. Considering the chances of disease being spread through asymptomatic transmission, social distancing has become a norm. This has brought a huge shift in how we live, work or interact with each other. It is feared that after the pandemic is over, the world would suffer a period of economic loss, as huge as the greatest depression of the 1930s or even more. With the world making medieval inventions and science doing wonders, we seem helpless to fight this pandemic. It has also drawn us to a realization that pandemic response cannot be extemporaneous.